2022
DOI: 10.1101/2022.01.03.22268599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody response to SARS-CoV-2 mRNA vaccine in lung cancer patients: Reactivity to vaccine antigen and variants of concern

Abstract: Purpose: We investigated SARS-CoV-2 mRNA vaccine-induced binding and live-virus neutralizing antibody response in NSCLC patients to the SARS-CoV-2 wild type strain and the emerging Delta and Omicron variants. Methods: 82 NSCLC patients and 53 healthy adult volunteers who received SARS-CoV-2 mRNA vaccines were included in the study. Blood was collected longitudinally, and SARS-CoV-2-specific binding and live-virus neutralization response to 614D (WT), B.1.617.2 (Delta), B.1.351 (Beta) and B.1.1.529 (Omicron) v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Initial data on Omicron neutralization in patients with cancer confirm the expected findings deduced from the general population 116 : the percentage of patients with solid tumours with neutralizing responses against Omicron increased from 47.8% to 88.9% following a third vaccine dose 117 . In particular, patients with non-small-cell lung cancer have a 79-fold lower neutralizing response to Omicron compared with individuals without cancer after two doses of an mRNA vaccine 118 . In patients with haematological malignancies, neutralizing antibodies against Omicron are rarely detected after two vaccine doses, although approximately 50% have detectable neutralizing antibodies after a third dose 119 .…”
Section: Vaccination In Patients With Cancermentioning
confidence: 99%
“…Initial data on Omicron neutralization in patients with cancer confirm the expected findings deduced from the general population 116 : the percentage of patients with solid tumours with neutralizing responses against Omicron increased from 47.8% to 88.9% following a third vaccine dose 117 . In particular, patients with non-small-cell lung cancer have a 79-fold lower neutralizing response to Omicron compared with individuals without cancer after two doses of an mRNA vaccine 118 . In patients with haematological malignancies, neutralizing antibodies against Omicron are rarely detected after two vaccine doses, although approximately 50% have detectable neutralizing antibodies after a third dose 119 .…”
Section: Vaccination In Patients With Cancermentioning
confidence: 99%
“…Pfizer claims in a recent press release that three doses provide significant protection, but there is no evidence to back up this claim 77 . The spread of SARS‐CoV‐2 Omicron variant has caused concern among cancer patients, according to Valanparambil et al Non‐small cell lung cancer patients had lower binding and live‐virus‐neutralizing antibody titers to SARS‐CoV‐2 mRNA vaccines than healthy vaccines, with significantly decreased live‐virus neutralization of the Delta and Omicron variants than the wild‐type strain 78 . The neutralizing potential of vaccine‐induced and hybrid immunity‐induced antibodies is significantly reduced in the Omicron variant.…”
Section: Vaccinesmentioning
confidence: 99%
“…77 The spread of SARS-CoV-2 Omicron variant has caused concern among cancer patients, according to Valanparambil et al Nonsmall cell lung cancer patients had lower binding and live-virusneutralizing antibody titers to SARS-CoV-2 mRNA vaccines than healthy vaccines, with significantly decreased live-virus neutralization of the Delta and Omicron variants than the wild-type strain. 78 The neutralizing potential of vaccine-induced and hybrid immunity-induced antibodies is significantly reduced in the Omicron variant. This could justify immune escape and high transmission despite extensive vaccination coverage.…”
Section: F I G U R E 5 Comparison Of Covid-19 Variants and Its Basic ...mentioning
confidence: 99%
“…Focusing on cancer patients and patients with autoimmune diseases, there are several studies that showed impaired antibody responses following dual COVID-19 vaccination in patients with chronic lymphocytic leukemia ( 81 ) and lung cancer ( 82 ). Furthermore, it was proved that humoral protection against the delta variant is markedly impaired among chronic lymphocytic leukemia patients, indicating the urgent need for further optimization of immune protection in this patient cohort ( 81 ).…”
Section: Methodsmentioning
confidence: 99%